The Australian economy : principles, policies and performance - McGillivray, Mark.; Padadopoulos, Theo. (Melbourne : Nelson, 1995)
This book is about: The nature and scope of economics; Demand and supply: the nature of markets; National income and accounting expenditure; ...
Keywords: Australia; Economics; Economics; Australia -- Economic conditions; Australia -- Economic policy